2020
DOI: 10.18502/npt.v7i2.2730
|View full text |Cite
|
Sign up to set email alerts
|

The effect of simulation-based education on nursing students’ knowledge and performance of adult basic cardiopulmonary resuscitation: A randomized clinical trial

Abstract: Background & Aim: Cardiopulmonary arrest as a life-threatening condition needs urgent interventions to protect individuals’ life and prevent irreversible damages to vital organs. This study aimed to investigate the effect of simulation-based education on the knowledge and performance of nursing students of adult essential life support cardiopulmonary resuscitation (BLS-CPR). Methods & Materials: This study used a pretest-posttest study with a control group. It was conducted at Iran University of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 20 publications
0
20
0
Order By: Relevance
“…In Table 1 , among the six included studies, two were from Turkey [ 12 , 14 ], one was from Japan, Brazil, Jordon, and Iran, respectively [ 11 , 13 , 15 , 16 ]. A total of 364 nursing students were enrolledin the included studies; of these, 186 underwent simulation, and 172 underwent the Traditional Teaching method at Undergraduate Nursing Schools.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In Table 1 , among the six included studies, two were from Turkey [ 12 , 14 ], one was from Japan, Brazil, Jordon, and Iran, respectively [ 11 , 13 , 15 , 16 ]. A total of 364 nursing students were enrolledin the included studies; of these, 186 underwent simulation, and 172 underwent the Traditional Teaching method at Undergraduate Nursing Schools.…”
Section: Resultsmentioning
confidence: 99%
“…3 . One study showed a high risk [ 11 ], Two studies [ 12 , 13 ] were at low risk, and three studies [ [14] , [15] , [16] ] were at unclear risk of bias for participant blinding, allocation concealment, and missing data [ Fig. 2 , Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that the realistic simulation was more effective than the traditional teaching method in increasing the knowledge (p = 0.001) and skill (p < 0.001) levels of students. Another pre-test and a post-test study conducted in Iran with 49 nursing students compared simulation-based education with traditional teaching and found that knowledge was significantly higher even after three months in the simulation group (p < 0.05) (33) .…”
Section: Discussionmentioning
confidence: 99%
“…The emergency department is the entrance door for patients to the hospital. The official statistics of Iran show that the emergency departments of different hospitals in the country accept about 30,000,000 patients every year and subject them to emergency procedures (3). It is obvious that the development and readiness of hospital emergency departments against disasters are of great importance and it is necessary for the government health care system to pay special attention to strengthening the various dimensions and pillars of this department in the field of proper response to accidents and disasters (4).…”
mentioning
confidence: 99%